The Caribbean dairy industry can benefit from India's successes - Aneja (Technical Centre for Agricultural and Rural Cooperation, 1993)
Dr Aneja is a dairy technologist. He was one of those responsible for planning and implementing the world`s largest dairy development project 'Operation Flood' in India. He is currently seeing up an Institute of Rural Management in New Delhi. Dr...